PENENTUAN HARGA POKOK PRODUKSI PERCETAKAN SABLON “OTAKKANAN production” di Yogyakarta - Ilham Ilham; Sudarno Sudarno (Diponegoro Journal of Accounting, 2013)
Small and Medium Enterprises is an industry that departs from the family or the home-based industry. Small and Medium Enterprises can be seen as a safety valve in the process of economic recovery, it is based on the role of Small and Medium Enterprises as the monetary crisis in 1998. Despite that Small and Medium Enterprises are still faced with the problem of Small and Medium Enterprises in the administrative process itself.One issue that arises is the report on the costs that determine the cost of production. According to one survey of Small and Medium Enterprises in Yogyakarta, which is engaged in printing services printing